The Development of The Chemical Teaching Material Integrated to Nautical Material to Improve Understanding The Hydrocarbon and Petroleum Concept in The Shipping Vocational High School (Journal of Innovative Science Education, 2020)
This research is development research aimed at producing chemically integrated teaching materials for commercial nautical vessels. The nautical vocational material for commercial vessels. namely ship machinery on the subject of the types of fuels and lubricants. is integrated into the subject matter of hydrocarbons and petroleum. In the subject matter of hydrocarbons and petroleum. vocational awareness of the environment and pollution prevention are also integrated. The study began with 4 stages. the phase define starts with identifying the needs of teaching materials in vocational voyage. at the stage design is made of teaching materials by integrating the two material vocational nautical commercial ships. stages develop are used to enhance the results of the phase design to validate and test of materials teach Validation used at this stage includes expert validation. readability and assessment. and trials to determine the response of students. The results of the study show that integrated chemistry teaching materials are very suitable to be used in chemical learning at the Vocational High School of Nautical. Based on the results of the analysis obtained a validity value of 3.72 (93%) with a very good category. for 94% of students showed a positive response to integrated chemistry teaching materials. The data obtained from the concept of understanding obtained tcount= 19.59> t0.05. 32= 1.699 in learning using integrated chemistry teaching materials showing an increase in understanding of concepts. The final stage of this research is the stage disseminate by publishing through journals and implementing teaching materials in schools.